DIVERSITY AND CORRELATION OF DEPTH AND HEIGHT DIMENSIONS BALI COW AT THE BALI CATTLE BREEDIN CENTER GEROGAK, BULELENG, BALI - Prama Putra, I Gede Bim Shiddi; Sampurna, I Putu; Suatha, I Ketut (Buletin Veteriner Udayana, 2022)
This study aims to determine the diversity and correlation between depth and height dimensions of bali cows based on depth and height dimensions of bali cattle and can be used as an indication in selecting bali cattle breeders at Pusat Pembibitan Sapi Bali Unggul (PPSBU) in Desa Gerokgak, Buleleng, Bali. The research object used consisted of 25 Bali cows in PPSBU. The data obtained were then analyzed by descriptive analysis to find the mean, standard deviation, and coefficient of variance. The correlation between the dimensions of depth and body height was analyzed by biplot analysis. The results obtained that the Bali cattle reared at PBSBU Gerogak, Buleleng, Bali had the greatest diversity (various) in the chest, which was 18.1191%, followed by the neck at 17, 5706%, the plank height was 16. ,1236%, 11.9739% in steering and the most uniform is body height, which is 5.3987%. Body height is positively correlated with deep neck and plank height, but not correlated with inside chest and in steering wheel, while plank height is correlated negative with in the chest and in the rudder.